Paving composition - Muniandy, Ratnasamy (2004)
The present invention relates to stone mastic asphalt compounds which are produced using a new technique and process. The process utilizes a specific aggregate gradation and matrix for high stability. Specially formulated fiber mastic asphalt is used to hold the aggregate in place while providing extended durability. This formulation is able to handle heavy loading from commercial vehicles and thus minimize pavement surface distresses. The use of the present invention is expected to reduce the cost of materials by about 15 to 20 percent